Transforming growth factor-β impairs glucocorticoid activity in the A549 lung adenocarcinoma cell line - Salem, S (Blackwell Publishing Ltd, 2012)
BACKGROUND AND PURPOSE: The lung adenocarcinoma cell line, A549, undergoes epithelial-mesenchymal cell transition (EMT) in response to TGF-β. Glucocorticoids do not prevent the EMT response, but TGF-β induced resistance to the cytokine-regulatory action of glucocorticoids. We sought to characterize the impairment of glucocorticoid response in A549 cells. EXPERIMENTAL APPROACH: A549 cells were exposed to TGF-β for up to 96 h before glucocorticoid treatment and challenge with IL-1α to assess glucocorticoid regulation of IL-6 and CXCL8 production. Nuclear localization of the glucocorticoid receptor α (GRα) was ascertained by immunofluorescence and Western blotting. Transactivation of the glucocorticoid response element (GRE) was measured with a transfected GRE-secreted human placental alkaline phosphatase reporter. KEY RESULTS: TGF-β (40–400 pM) reduced the maximum inhibitory effect of dexamethasone on IL-1α-induced IL-6 and CXCL8 production. The impaired glucocorticoid response was detected with 4 h of TGF-β (40 pM) exposure (and 4 h IL-1α to induce CXCL8 expression) and therefore was not secondary to EMT, a process that requires longer incubation periods and higher concentrations of TGF-β. TGF-β also impaired dexamethasone regulation of granulocyte-macrophage colony-stimulating factor in thrombin-stimulated BEAS-2B epithelial cells. Impaired regulation of CXCL8 was associated with markedly reduced GRE transactivation and reduced induction of mRNA for IκBα, the glucocorticoid-inducible leucine zipper and the epithelial sodium channel (SCNN1A). The expression, cellular levels and nuclear localization of GRα were reduced by TGF-β. CONCLUSIONS AND IMPLICATIONS: We have identified mechanisms underlying the impairment of responses to glucocorticoids by TGF-β in the A549 and BEAS-2B cell lines.